Managing Wildlife Habitat: Complex Interactions With Biotic and Abiotic Disturbances - Leclerc, Marc-Antoine F.; Daniels, Lori D.; Carroll, Allan L. (Frontiers in Ecology and Evolution, 2021)
Sustainable forest management strategies include emulating historical disturbance regimes to achieve multiple objectives. Partial-harvesting strategies are used to overcome conflicts between timber production and wildlife habitat conservation; however, the potential impacts on complex disturbance interactions and ecological functions remain largely unknown. In 1984, a controlled experiment was initiated in the dry forests of central British Columbia, Canada, to test partial harvesting intended to enhance mule deer habitat while allowing timber extraction. To determine the short- and long-term impacts on complex disturbance regimes, we quantified changes in forest structure and susceptibility to western spruce budworm, Douglas-fir beetle, and wildfire. We compared structural attributes in 2014 (30 years after the first harvest) and 2015 (1 year after the second harvest) in treated forests, and contrasted them with control forests that were measured in 2015. In the short term (1 year post-harvest), partial harvesting altered forest structure by reducing total canopy cover, subcanopy tree density and basal area, and increasing the abundance of large woody surface fuels. In the long term (30 years post-harvest), the forest canopy attributes did not differ between the treatment and control areas, partly due to increased growth of subcanopy trees. Harvesting had little impact on forest susceptibility to western spruce budworm. Susceptibility to Douglas-fir beetle was lower in the short term due to fewer available mature host trees, but increased to levels similar to the control forest over the long term. Reduced canopy fuels and increased canopy base height decreased the likelihood of crown fire in favour of surface fire. In the long term, canopy fuels and likelihood of crown fire recovered, but woody fuel loads remained low after 30 years. Harvesting to enhance mule deer habitat interacts with biotic and abiotic disturbances in the short and long term. Potential cascading affects depended more on the decision to remove harvesting residuals to mitigate potential Douglas-fir beetle infestations and wildfire than on time since treatment. Provided partial harvesting occurs at intervals ≤30 years and residuals are immediately removed, timber extraction and mule deer habitat can be compatible with complex disturbance regimes and sustainable forest management.